Locational preferences and spatial arrangement in the barrow landscape of Serra do Barbanza (North-western Iberia). (June 2020) - Carrero-Pazos, Miguel; Bustelo-Abuín, Julián; Barbeito-Pose, Víctor; Rodríguez-Rellán, Carlos
Highlights: Traditional hypotheses of megalithic location are discussed. Environmental variables are analysed through site predictive modelling. The clustering of sites is investigated through second-order modelling. Sites show an aggregation at local scales explained by intended site-spacing dynamics. Abstract: As anywhere else around the world, GIS is an essential tool in Galician Archaeology (NW Spain) when examining and analysing spatial data. This is also true for the study of mounds in that area, since spatial analysis and statistics have become increasingly used for contrasting hypotheses regarding the locational preferences of these monuments, usually inferred from observations made during fieldwork or taken from studies conducted elsewhere. Drawing on this basis, in this paper, we have analysed the locational patterns of the tumuli of the upper tracts of the Serra do Barbanza (Galicia, NW Spain). Using a site-predictive modelling approach, several environmental covariates were analysed in order to explore their potential role in explaining the distribution of prehistoric mounds in the area. Subsequently, we studied the clustering of these monuments via second-order modelling. Our results suggest that tumuli in the Serra do Barbanza tended to cluster on a very local scale, a trend that can only be explained by intended site spacing strategies that may have taken place over millennia. Finally, by using significance testing via Monte Carlo Simulation, we have modelled both the effect of possible preferences regarding the location of mounds and the potential impact of tradition, with pre-existent megaliths possibly fostering the construction of more monuments in the nearby areas.